Cultural Wisdom of the Samin Tribe as a Foundation for Multicultural Counseling Practices - Faizin, Muhammad; Budianto, Ahmad (International Journal of Multicultural Counseling and Development, 2025)
Stereotypes held by counselors can negatively influence the selection of service interventions and hinder the effectiveness of counseling. Therefore, strengthening multicultural understanding is essential to shaping counselor character that reflects openness, sensitivity, and responsiveness to cultural diversity. This study aims to explore the characteristics of multicultural counselors by integrating noble cultural values of the Samin tribe in Bojonegoro, Indonesia, with multicultural counseling competencies. The research employed a Systematic Literature Review (SLR) using the PRISMA model. A total of 120 articles were initially collected from various sources, including journals, books, and reputable conference proceedings indexed in Scopus and Google Scholar. Following a rigorous screening process based on predefined inclusion and exclusion criteria, 14 articles were identified as eligible for further analysis. Data were analyzed through thematic content analysis to identify cultural values relevant to counselor competencies. The findings highlight three key values of Samin teachings: (1) angger-angger pengucap (wise use of words), which aligns with effective communication and cultural sensitivity; (2) angger-angger pertikel (appropriate behavior), which relates to ethical conduct and counselor integrity; and (3) angger-angger lakunono (adherence to norms), which supports counselors’ commitment to justice and cultural respect. These values, when applied, can enhance counselors’ multicultural competencies, particularly in fostering non-judgmental attitudes and empathy toward diverse clients. The implication of this study is that integrating local wisdom, such as the Samin tribe’s cultural values, offers a contextualized approach for developing the character of multicultural counselors, making them more relevant and effective in addressing the challenges of today’s diverse societies.